Extracellular vesicles in the rhizosphere: targets to improve nutrient use efficiency of crops? - Paponov, Ivan A.; Schulz, Stefanie; Schloter, Michael; Conesa, Ana; Leshem, Yehoram (Frontiers in Plant Science, 2025)
Nutrient use efficiency (NUE) is central to sustainable agriculture, yet major crops such as wheat or barley typically take up only about half of applied fertilizer. The rest is lost through leaching or gaseous emissions, contributing to environmental pollution and climate change. Root exudates play a key role in shaping microbial communities and their functions at the plant–soil interface, catalyzing nutrient mobilization, immobilization, and uptake. Whereas most studies in the past focused on sugars, amino acids, and organic acids excreted by roots, recent evidence highlights extracellular vesicles (EVs) as specialized carriers of proteins, metabolites, and small RNAs (sRNAs) that regulate microbial communities in the rhizosphere. Proteomic studies show that plant EVs contain nutrient transporters, proton ATPases, and aquaporins in their membranes. Once secreted, these vesicles may buffer ions, acidify the microenvironment, or send signals to microbes. Here we discuss the potential of EVs to influence microbes driving crop NUE. We show that EVs carry sRNAs that regulate microbial genes involved in nitrogen cycling, and that plant miRNAs control internal responses to nutrient status. Together, these mechanisms may allow plants to align internal nutrient demand with rhizosphere processes and reduce nitrogen losses from soil. Identifying EV cargo that enhances microbial nutrient turnover or minimizes nutrient losses could guide future breeding. Crop genotypes selected for optimized EV secretion may shape beneficial microbial communities, leading to higher NUE, reduced fertilizer dependence, and lower N2O emissions. Therefore, EV-mediated signaling may be considered a promising new breeding target for sustainable crop improvement.